Completing the banking union: Economic requirements and legal conditions - Thorsten Beck; Jan Pieter Krahnen; Philippe J. Martin; Franz C. Mayer; Jean Pisani-Ferry; Tobias Tröger; Beatrice Weder; Nicolas Véron; Jeromin Zettelmeyer (Leibniz Institute for Financial Research SAFE, 2022)
The great financial crisis and the euro area crisis led to a substantial reform of financial safety nets across Europe and - critically - to the introduction of supranational elements. Specifically, a supranational supervisor was established for the euro area, with discrete arrangements for supervisory competences and tasks depending on the systemic relevance of supervised credit institutions. A resolution mechanism was created to allow the frictionless resolution of large financial institutions. This resolution mechanism has been now complemented with a funding instrument. While much more progress has been achieved than most observers could imagine 12 years ago, the banking union remains unfinished with important gaps and deficiencies. The experience over the past years, especially in the area of crisis management and resolution, has provided impetus for reform discussions, as reflected most lately in the Eurogroup statement of 16 June 2022.
urn:nbn:de:hebis:30:3-651877
Keywords: 330; Banking Union; Legal Reforms